2023
DOI: 10.1186/s42836-022-00157-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of different levels of constraint in TKA during daily activities

Abstract: Background Numerous total knee prosthetic implants are currently available on the orthopedic market, and this variety covers a set of different levels of constraint: among the various models available, a significant role is covered by mobile bearing cruciate-retaining design with an ultra-congruent insert, mobile bearing cruciate-retaining design, fixed-bearing posterior stabilized prosthesis and fixed-bearing constrained condylar knee. A biomechanical comparative study among them could therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…The results showed that the contact area of the mobile-bearing prosthesis polyethylene insert was 400-800 mm 2 , while that of the fixed-bearing prosthesis polyethylene insert was 200-250 mm 2 . The findings confirmed that the contact area of the tibiofemoral joint of the mobile-bearing prosthesis was higher than that of the fixedbearing prosthesis; thus, the contact stress of the mobile-bearing prosthesis was lower than that of the fixed-bearing prosthesis because the contact pressure was inversely proportional to the contact area Castellarin et al (2023) (Table 1). Stukenborg-Colsman et al (2002) performed an FEA study on cadavers and reached the same conclusion: compared with fixed-bearing prostheses, mobile-bearing prostheses maximized the contact area of the tibiofemoral joint and reduced the peak contact pressure, so that the mobile-bearing prosthesis polyethylene insert provides more movement for the prosthesis and minimizes polyethylene wear compared to the fixed-bearing prosthesis model (Heesterbeek et al, 2018;Andreani et al, 2020), resulting in improved implant survival and performance.…”
Section: Application Of Fea In Prosthesis Materials and Designsupporting
confidence: 67%
See 1 more Smart Citation
“…The results showed that the contact area of the mobile-bearing prosthesis polyethylene insert was 400-800 mm 2 , while that of the fixed-bearing prosthesis polyethylene insert was 200-250 mm 2 . The findings confirmed that the contact area of the tibiofemoral joint of the mobile-bearing prosthesis was higher than that of the fixedbearing prosthesis; thus, the contact stress of the mobile-bearing prosthesis was lower than that of the fixed-bearing prosthesis because the contact pressure was inversely proportional to the contact area Castellarin et al (2023) (Table 1). Stukenborg-Colsman et al (2002) performed an FEA study on cadavers and reached the same conclusion: compared with fixed-bearing prostheses, mobile-bearing prostheses maximized the contact area of the tibiofemoral joint and reduced the peak contact pressure, so that the mobile-bearing prosthesis polyethylene insert provides more movement for the prosthesis and minimizes polyethylene wear compared to the fixed-bearing prosthesis model (Heesterbeek et al, 2018;Andreani et al, 2020), resulting in improved implant survival and performance.…”
Section: Application Of Fea In Prosthesis Materials and Designsupporting
confidence: 67%
“…However, biomechanical problems such as prosthesis loosening, periprosthetic fracture and prosthesis wear after knee arthroplasty remain to be solved ( Wang et al, 2021 ). At present, FEA models can be observed at any angle, and operations on the model, such as determining the osteotomy thickness, analysing the stress of different prosthetic materials ( Castellarin et al, 2023 ), and measuring the alignment between prostheses, can be simulated. FEA methods can overcome the shortcomings of traditional mechanical research methods, such as the long cycles, non-repeatable operations and high costs.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies mainly report the results of unconstrained prostheses. Among the different types of TKA, posterior-stabilized (PS) constraints TKA is popular due to its potential for increased stability [11]. Currently, it is one of the most widely implanted TKA, representing 20%-50% of implants in implant registries [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is one of the most widely implanted TKA, representing 20%-50% of implants in implant registries [2,3]. The posterior-stabilized designs are classified as partially constrained compared to cruciate retaining implants, as they aim to substitute the PCL with a post-cam system to provide a more stable component interface [11]. PS TKA has demonstrated excellent lifetime survivorship in cemented TKA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation